2010
DOI: 10.21273/jashs.135.4.317
|View full text |Cite
|
Sign up to set email alerts
|

Insertion and Characterization of the cry1Ia1 Gene in the Potato Cultivar Spunta for Resistance to Potato Tuber Moth

Abstract: Potato tuber moth (Phthorimaea operculella) is a serious pest of potatoes in tropical and subtropical regions of the world, including South Africa. The cry1Ia1 gene (from Bacillus thuringiensis) under the control of the 35S cauliflower mosaic virus promoter was transformed into the potato (Solanum tuberosum) cultivar Spunta to develop a cultivar with resistance to potato tuber moth for release in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The acute toxicity test established a no adverse effect level (NOAEL) of 2000 mgÁkg -1 body weight per day, from which an ADI of 20 mgÁkg -1 body weight per day was calculated (Benford, 2000). Using the expression levels of Cry1Ia1 in 'SpuntaG2' tubers [0.12 mgÁg -1 fresh weight (Zarka et al, 2010)], the expected dose of Cry1Ia1 consumed by the South African population can be estimated. The South African Medical Research Council (2002) estimates average adult consumption of potatoes at 7.9 gÁkg -1 body weight per day.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The acute toxicity test established a no adverse effect level (NOAEL) of 2000 mgÁkg -1 body weight per day, from which an ADI of 20 mgÁkg -1 body weight per day was calculated (Benford, 2000). Using the expression levels of Cry1Ia1 in 'SpuntaG2' tubers [0.12 mgÁg -1 fresh weight (Zarka et al, 2010)], the expected dose of Cry1Ia1 consumed by the South African population can be estimated. The South African Medical Research Council (2002) estimates average adult consumption of potatoes at 7.9 gÁkg -1 body weight per day.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, 'SpuntaG2', a potato cultivar containing the cry1Ia1 gene, was extensively characterized at the molecular level (Zarka et al, 2010). The results indicated that the cry1la1 gene in 'SpuntaG2' was unchanged during the transformation process, was stably integrated into the potato 10 1 0 0 1 1 1 2 10 2 0 0 1 2 2 2 100 1 0 0 1 2 2 1 100 2 0 0 1 2 2 2 0 1 2 2 1 2 z Each well contained 1mL of diet, the designated amount of Cry1Ia1 protein, and two newly hatched M. sexta larvae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant Material The potato variety 'Spunta' was transformed using vector constructs designed to constitutively express the cry1Ia1 gene as described in Li et al (1999) and Zarka et al (2010). Tubers of these transformed Spunta lines ('SpuntaG2', 'SpuntaG3' and 'Spunta6a3') were produced under field conditions by the Michigan State University Potato Breeding Program and held at 3°C prior to use in bioassays.…”
Section: Methodsmentioning
confidence: 99%